Knowledge Structures of City Innovation Systems: Singapore and Hong Kong - Wong, Chan Yuan; Ng, Boon Kwee; Azizan, Suzana Ariff; Hasbullah, Maisarah (Taylor & Francis, 2018)
Cities are naturally the center of attention when innovation and its geography are discussed. This paper seeks to elucidate the knowledge structures of the city innovation systems of Hong Kong and Singapore, and shed light on the performance of knowledge production, networks, and features in accordance with: (1) patent portfolios and fields of technology; (2) the patent landscape; and (3) the correlation map between fields and entities that produce patents. Findings indicate that private firms dominate the patenting landscape for the selected economies. Scientific activities performed by universities and public research institutions are converging with technological knowledge performed by firms. Hong Kong and Singapore sought to attain a co-evolution process for science-based industrial development.